Pengaruh Pemberian Kompres Hangat Air Rebusan Serai (Cymbopogon Citratus) terhadap Penurunan Nyeri Arthritis Gout di Puskesmas Merdeka Palembang - Lela Aini; Dwi Noviyanti; Tini Yurika (Universitas Malahayati Lampung, 2023)
ABSTRACT Based on data from the World Health Organization (WHO), the number of Gout disease reaches 4.75% of 10% of the population. Symptoms that often arise in Arthritis Gout are mono-articular (attacking one joint) accompanied by swelling, redness, severe pain, treatment of Gout arthritis can be done with pharmacological and non-pharmacological therapies that can be done, among others, using herbal plants, and relaxation techniques (warm compresses). This study was to determine the effect of giving warm compresses with boiled lemongrass (Cymbopogon Citratus) on the reduction of Gout arthritis pain at Public Health Center Merdeka in Palembang. Used one-group pre and post test. All Arthritis Gout patients who will be given a warm compress of lemongrass boiled water (cymbopogon citratus) at the Merdeka Palembang Health Center in 2022 in January-March are 209 people. Sampling in this study was conducted by purposive sampling with a total sample of 34 respondents. Data analysis used univariate and bivariate analysis. Showed that the average Gout pain before giving lemongrass boiled water compresses (cymbopogon citratus) was 5 and after giving lemongrass boiled water compresses (cymbopogon citratus) was 3. The results of statistical tests are known to obtain a p value of 0.000 0.05. There’s an effect of giving a warm compress of lemongrass boiled water (cymbopogon citratus) on reducing Gout arthritis pain at the Public Health Center Merdeka Palembang at 2022. Keywords: Gout Arthritis, Pain, Warm Compress Lemongrass Boiled Water ABSTRAK Berdasarkan data World Health Organization (WHO), angka penyakit asam urat mencapai 4,75% dari 10% populasi. Gejala yang sering timbul pada penyakit Arthritis Gout yang bersifat monoartikular (menyerang satu sendi) disertai pembengkakan, kemerahan dan nyeri hebat. Penanganan Arthritis Gout dapat dilakukan dengan terapi farmakologi dan non farmakologi yang dapat dilakukan antara lain menggunakan tanaman herbal dan teknik relaksasi (kompres hangat). Mengetahui Pengaruh Pemberian Kompres Hangat Air Rebusan Serai (Cymbopogon Citratus) Terhadap Penurunan Nyeri Arthritis Gout di Puskesmas Merdeka Palembang. Menggunakan One-group pre and post test pada seluruh pasien Arthritis Gout yang akan diberikan kompers hangat air rebusan serai (cymbopogon citratus) di Puskesmas Merdeka Palembang pada tahun 2022 bulan Januari-Maret sebanyak 209 orang. Pengambilan sampel dalam penelitian ini dilakukan dengan purposive sampling dengan jumlah sampel sebanyak 34 responden. Analisa data menggunakan analisa univariat dan bivariat. Penelitian didapatkan rerata nyeri Arthritis Gout sebelum dilakukan pemberian kompres air rebusan serai (cymbopogon citratus) yaitu 5 dan sesudah dilakukan pemberian kompres air rebusan serai (cymbopogon citratus) yaitu 3. Hasil uji statistik diketahui diperoleh nilai p value sebesar 0,000α 0,05. Ada pengaruh pemberian kompres hangat air rebusan serai (cymbopogon citratus) terhadap penurunan nyeri Arthritis Gout di Puskesmas Merdeka Palembang tahun 2022. Kata Kunci: Arthritis Gout, Nyeri, Kompres Hangat Air Rebusan Serai